Longitudinal validation of the Brief Index of Lupus Damage (BILD) - Katz, Patricia (2014)
OBJECTIVE: To provide further validation of the Brief Index of Lupus Damage (BILD), assessing its sensitivity to change in disease status and ability to predict mortality risk. METHODS: Data were from the UCSF Lupus Outcomes Study (LOS; n=958), in which the BILD was administered twice, approximately 5 years apart. We examined disease activity and health care utilization among participants who completed the BILD twice (n=745). We identified increases in disease activity and utilization that would suggest a disease flare between the two BILD administrations and compared their occurrence by BILD score increases (0, 1, 2, 3, >3). Deaths were ascertained when annual interviews were attempted. Kaplan-Meier life-table analysis compared mortality rates for four groups of initial BILD scores (0, 1, 2, ≥3), and differences were tested using a log-rank test. Using Cox proportional hazard models, we estimated risk of death associated with higher BILD scores. RESULTS: BILD score increases were associated with spikes in disease activity (p=0.05) and physician visits (p=0.004) over baseline, and with hospitalizations (p<0.001) during the intervening years. Of those with BILD score increases >3, 84% were hospitalized prior to the second BILD. During follow-up there were 60 deaths (6.3%). BILD scores of 2 (hazard ratio: 6.1 [95% confidence interval 1.3–30.0]) and ≥3 (10.8 [2.5–46.2]) were associated with higher risk of death. CONCLUSION: This analysis provides evidence of the BILD’s predictive validity and ability to detect change. While not intended to replace clinical evaluation of disease damage, the BILD appears to be a useful tool for research.